Extraction and characterisation of quebracho (Schinopsis sp.) tannins - Tonello, M. L. (1998)
Vegetables tarmins are organic substances; when considering the great number of different tarmins, it is possible to State certain properties which are common to all of them such as: a high molecular weight, causing colloidal Solutions in which the particles of tarmins are present in all forms of dispersions; a great number of free hydroxy phenolic groups, which are mainly responsable for the solubility of tannins in water; with few exceptions, all tarmins are amorphous and no crystalline; a different degree of acidity resultant from the polarity of the hydroxy phenolic groups which in some cases is enhanced by free carboxyl groups; tarmins formed by esterification of carboxyl groups usually exhibit a higher acidity than those made by condensation or polymerisation of components free from carboxyl groups; formation of intense precipitates in the presence of soluble iron (III) salís, etc. This last property of the tarmins, that is the capacity of forming chelates with the hexahydrated iron (III) ion, could be employed efficiently to modify the kinetic of oxidation of iron and Steel substraía. In this paper, the extraction, the purification, the concentration and the characterisation of tannins obtained from quebracho (Schinopsis sp.) were performed, particularly with the objective of knowing some inherent properties to the reaction between the tarmins and the iron.